Modeling Pharmacokinetic Profiles of Insulin Regimens to Enhance Understanding of Subcutaneous Insulin Regimens. (10th April 2017) - Tham, Lai San; Schneck, Karen; Ertekin, Ali; Reviriego, Jesus
Abstract: Insulin pharmacokinetics following subcutaneous administration were modeled, simulated, and displayed through an interactive and user‐friendly interface to illustrate the time course of administered insulins frequently prescribed, providing a simple tool for clinicians through a straightforward visualization of insulin regimens. Pharmacokinetic data of insulin formulations with different onset and duration of action from several clinical studies, including insulin glargine, regular insulin, neutral protamine Hagedorn (NPH), insulin lispro, and premixed preparations of NPH with regular insulin (Mix 70/30), and insulin lispro protamine suspension with insulin lispro (Mix 50/50, Mix 75/25), were used to develop a predictive population pharmacokinetic model of insulins with consideration of factors such as insulin formulation, weight‐based dosing, body‐weight effect on volume of distribution, and administration time relative to meals, on the insulin time‐action profile. The model‐predicted insulin profile of each insulin was validated and confirmed to be comparable to observed data via an external validation method. Model‐based simulations of clinically relevant insulin‐dosing scenarios to cater to specific initial patient and prescribing conditions were then implemented with differential equations using the R statistical program (version 3.2.2). The R package Shiny was subsequently applied to build a web browser interface to execute and visualize the model simulation outputs. The application of insulin pharmacokinetic modeling enabled informative visualization of insulin time‐action profiles and provided an efficient and intuitive educational tool to quickly convey and interactively explore many insulin time‐action profiles to ease the understanding of insulin formulations in clinical practice.